Synthesis and electrochemical performance of 0.6Li3V2(PO4)3·0.4Li–V–O composite cathode material for lithium ion batteries. (10th April 2015) - Li, Y.; Bai, W.Q.; Wang, D.H.; Niu, X.Q.; Zhang, Y.D.; Tang, H.; Wang, X.L.; Gu, C.D.; Tu, J.P.
Abstract: A novel 0.6Li3 V2 (PO4 )3 ·0.4Li–V–O composite cathode material is synthesized by sol-gel method followed by solvothermal and solid state reaction. The morphology and structure of the composite are characterized by scanning electron microscopy (SEM), transmission electron microscopy (TEM), X-ray diffraction (XRD) and X-ray photo-electron spectroscopy (XPS). The composite particles are well-crystallized and present uniform nanoplate alike. Except Li3 V2 (PO4 )3 phase, LiV2 O5 and VO2 are also present in the composite. The 0.6Li3 V2 (PO4 )3 ·0.4Li–V–O electrode delivers a discharge capacity of 149.3 mAh g −1 at 50 mAg −1 between 2.0 V and 4.3 V, and has higher rate property than Li3 V2 (PO4 )3 . The diffusion coefficients of Li ions in the composite are in the range of 10 −9.5  − 10 −7.5  cm 2  s −1 obtained from galvanostatic intermittent titration technique (GITT).